Whole-body magnetic resonance imaging provides accurate staging of diffuse large B-cell lymphoma, but is less preferred by patients - Lambert, Lukas; Wagnerova, Monika; Vodicka, Prokop; Benesova, Katerina; Zogala, David; Trneny, Marek; Burgetova, Andrea (World journal of radiology, 2025)
BACKGROUND: Whole-body magnetic resonance imaging (wbMRI) allows general assessment of systemic cancers including lymphomas without radiation burden. AIM: To evaluate the diagnostic performance of wbMRI in the staging of diffuse large B-cell lymphoma (DLBCL), determine the value of individual MRI sequences, and assess patients' concerns with wbMRI. METHODS: In this single-center prospective study, adult patients newly diagnosed with systemic DLBCL underwent wbMRI on a 3T scanner [diffusion weighted images with background suppression (DWIBS), T2, short tau inversion recovery (STIR), contrast-enhanced T1] and fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) (reference standard). The involvement of 12 nodal regions and extranodal sites was evaluated on wbMRI and PET/CT. The utility of wbMRI sequences was rated on a five-point scale (0 = not useful, 4 = very useful). Patients received a questionnaire regarding wbMRI. RESULTS: Of 60 eligible patients, 14 (23%) were enrolled and completed the study. The sensitivity of wbMRI in the nodal involvement (182 nodal sites) was 0.84, with 0.99 specificity, positive predictive value of 0.96, negative predictive value of 0.97, and 0.97 accuracy. PET/CT and wbMRI were concordant both in extranodal involvement (13 instances) and staging (κ = 1.0). The mean scores of the utility of MRI sequences were 3.71 ± 0.73 for DWIBS, 2.64 ± 0.84 for T1, 2.14 ± 0.77 for STIR, and 1.29 ± 0.73 for T2 (P < 0.0001). Patients were mostly concerned about the enclosed environment and duration of the MRI examination (27% of patients). CONCLUSION: The wbMRI exhibited excellent sensitivity and specificity in staging DLBCL. DWIBS and contrast-enhanced T1 were rated as the most useful sequences. Patients were less willing to undergo wbMRI as a second examination parallel to PET/CT, especially owing to the long duration and the enclosed environment.
Keywords: Magnetic resonance imaging; Positron emission tomography/computed tomography; Diffuse large B-cell lymphoma; Preference; Staging